The Effect Of Laundry Chemical Dose On The Quality Of Cleaning Medical Linen In The Regional Public Hospital Of Kediri District - Slamet Hariadi; Yuly Peristiowati (Journal of Hospital Management and Services, 2021)
Contaminated linen can produce large amounts of pathogenic microorganisms. In particular, handling dirty linen is very important to reduce the risk of nosocomial infections. The problems that occur due to nosocomial infections are very complex and can cause losses for patients and hospitals. In addition, unclean washing will leave stains and odors from previous patients so that it can cause discomfort to patients who use it later. The purpose of this study was to analyze the effect of laundry chemical doses on the quality of cleanliness of medical linen at the kediri district general hospital. The design of this study was an experimental quantitative study with a true experimental post test only design approach. With the focus of the research directed to analyze the effect of laundry chemical doses on the quality of cleanliness of medical linen at the kediri district general hospital with a sample of 74 samples taken using the accidental sampling technique. The findings showed that based on the mann whitney test, the value of 0.000 <0.05 was obtained so that it can be concluded that there is an effect of the laundry chemical dose on the quality of the smell of medical linen at the kediri district general hospital. And also obtained a value of 0.001 <0.05 so that it can be concluded that there is an effect of the laundry chemical dose on the visual quality of medical linen at the kediri district general hospital. The provision of laundry chemicals on medical linen in both infectious and non-infectious categories can effectively improve the quality of cleanliness of medical linen and can be proven by the quality of the fresh smell and the visual quality that looks clean.